The Exeter Activity Unlimited statement on physical activity and exercise for cystic fibrosis: methodology and results of an international, multidisciplinary, evidence-driven expert consensus. (23rd August 2022) - Williams, Craig A; Barker, Alan R; Denford, Sarah; van Beurden, Samantha B; Bianchim, Mayara S; Caterini, Jessica E; Cox, Narelle S; Mackintosh, Kelly A; McNarry, Melitta A; Rand, Sarah; Schneiderman, Jane E; Wells, Greg D; et al.
Background: The roles of physical activity (PA) and exercise within the management of cystic fibrosis (CF) are recognised by their inclusion in numerous standards of care and treatment guidelines. However, information is brief, and both PA and exercise as multi-faceted behaviours require extensive stakeholder input when developing and promoting such guidelines. Method: On 30 th June and 1 st July 2021, 39 stakeholders from 11 countries, including researchers, healthcare professionals and patients participated in a virtual conference to agree an evidence-based and informed expert consensus about PA and exercise for people with CF. This consensus presents the agreement across six themes: (i) patient and system centred outcomes, (ii) health benefits, iii) measurement, (iv) prescription, (v) clinical considerations, and (vi) future directions. The consensus was achieved by a stepwise process, involving: (i) written evidence-based synopses; (ii) peer critique of synopses; (iii) oral presentation to consensus group and peer challenge of revised synopses; and (iv) anonymous voting on final proposed synopses for adoption to the consensus statement. Results: The final consensus document includes 24 statements which surpassed the consensus threshold (>80% agreement) out of 30 proposed statements. Conclusion: This consensus can be used to support health promotion by relevant stakeholders for people with CF.